Case Report: Expressive Speech Disorder in a Family as a Hallmark of 7q31 Deletion Involving the FOXP2 Gene - Nagy, Orsolya; Kárteszi, Judit; Elmont, Beatrix; Ujfalusi, Anikó (Frontiers in Pediatrics, 2021)
Pathogenic variants of FOXP2 gene were identified first as monogenic cause of childhood apraxia of speech (CAS), a complex disease that is associated with impairment of precision and consistency of movements underlying speech, due to deficits in speech motor planning and programming. FOXP2 variants are heterogenous, single nucleotide variants and small insertions/deletions, intragenic and large scale deletions, as well as disruptions by structural chromosomal aberrations and uniparental disomy of chromosome 7 are the most common types of mutations. FOXP2-related speech and language disorders can be classified as “FOXP2-only”, wherein intragenic mutations result in haploinsufficiency of the FOXP2 gene or “FOXP2-plus” generated by structural genomic variants (i.e. translocation, microdeletion, etc.) and having more likely developmental and behavioural disturbances adjacent to speech and language impairment. The additional phenotypes are usually related to the disruption/deletion of multiple genes neighbouring FOXP2 in the affected chromosomal region. We report the clinical and genetic findings in a family with four affected individuals having expressive speech impairment as the dominant symptom and additional mild dysmorphic features in three. A 7.87 Mb interstitial deletion of the 7q31.1q31.31 region was revealed by whole genome diagnostic microarray analysis in the proband. The FOXP2 gene deletion was confirmed by multiplex ligation-dependent probe amplification (MLPA) and all family members were screened by this targeted method. The FOXP2 deletion was detected in the mother and two siblings using MLPA. Higher resolution microarray was performed in all affected individuals to refine the extent and breakpoints of the 7q31 deletion and to exclude other pathogenic copy number variants. To the best of our knowledge, there are as yet only two family-studies reported to date with interstitial 7q31 deletion and showing the core phenotype of FOXP2 haploinsufficiency. Our study may contribute to better understanding of the behavioural phenotype of FOXP2 disruptions and aid in identification of such patients. We illustrate the importance of targeted MLPA analysis suitable for detection of FOXP2 deletion in selected cases with specific phenotype of expressive speech disorder. The “phenotype first” and targeted diagnostic strategy can improve the diagnostic yield of speech disorders in the routine clinical practice.